An algorithm to enumerate all possible protein conformations verifying a set of distance constraints - Cassioli, Andrea; Bardiaux, Benjamin; Bouvier, Guillaume; Mucherino, Antonio; Alves, Rafael; Liberti, Leo; Nilges, Michael; Lavor, Carlile; Malliavin, Thérèse E (BMC bioinformatics, 2015)
Background The determination of protein structures satisfying distance constraints is an important problem in structural biology. Whereas the most common method currently employed is simulated annealing, there have been other methods previously proposed in the literature. Most of them, however, are designed to find one solution only. Results In order to explore exhaustively the feasible conformational space, we propose here an interval Branch-and-Prune algorithm ( i BP) to solve the Distance Geometry Problem (DGP) associated to protein structure determination. This algorithm is based on a discretization of the problem obtained by recursively constructing a search space having the structure of a tree, and by verifying whether the generated atomic positions are feasible or not by making use of pruning devices. The pruning devices used here are directly related to features of protein conformations. Conclusions We described the new algorithm i BP to generate protein conformations satisfying distance constraints, that would potentially allows a systematic exploration of the conformational space. The algorithm i BP has been applied on three α -helical peptides.